Predicting Bankruptcy of an IDX Acceleration Board Firm Using the Altman Z”-Score Model - Dewi, Resti Kartika (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2025)
This study aims to predict the bankruptcy level of companies using the Altman Z”-Score Model. The research population consists of companies listed on the Acceleration Board of the Indonesia Stock Exchange (IDX) during the 2021–2024 period, with PT. Falmaco Nonwoven Industri Tbk as the sample. The data used were financial statements from 2022–2024 obtained from the official IDX website. The results show that the Z”-Score values of PT. Falmaco Nonwoven Industri Tbk during the 2022–2024 period consistently remained below the safe threshold and were categorized in the Distress zone (Z” < 1.1). In 2022, the Z”-Score was recorded at -4.00, mainly due to negative contributions from the ratios of working capital, retained earnings, and EBIT to total assets, with only a slight positive contribution from the equity-to-liabilities ratio. In 2023, the Z”-Score improved to -3.27, primarily due to improvements in the equity-to-liabilities ratio, although other ratios continued to provide dominant negative contributions. Further improvement occurred in 2024, with the Z”-Score reaching -2.50, supported by a stronger capital structure. Nevertheless, retained earnings and EBIT to total assets still showed significant negative contributions, leaving the company in a distress condition. This study confirms that the Altman Z”-Score Model is relevant as a bankruptcy prediction tool for companies on the IDX Acceleration Board and provides important insights for management, investors, and stakeholders in making strategic decisions.